2013
DOI: 10.1002/pola.26701
|View full text |Cite
|
Sign up to set email alerts
|

Seleno‐containing poly(vinyl acetate) prepared by diselenocarbonates‐mediated controlled free radical polymerizations

Abstract: The living free radical polymerizations of vinyl acetate (VAc) were successfully achieved in the presence of a novel organic selenium compound (diselenocarbonates), with 2,2 0 -azobisisobutyronitrile (AIBN) as the initiator. The living characteristics of the VAc polymerization were confirmed by the linear first-order kinetic plots and linear increase of molecular weights (M n ) of the polymers with monomer conversions, while keeping the relatively low molecular weight distributions.In addition, the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…However, due to the limitation of selenide group, the polymerization showed limited controllability on the structure of polymers. Our group has reported the LRP of vinyl monomers based on the diselenocarbonyl compounds, e.g., selenium‐mediated radical polymerization (SeRP) . Such system showed moderate to well‐controlled polymerization behavior for most of the vinyl monomers, such as styrene, (meth)acrylates, vinyl acetate, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the limitation of selenide group, the polymerization showed limited controllability on the structure of polymers. Our group has reported the LRP of vinyl monomers based on the diselenocarbonyl compounds, e.g., selenium‐mediated radical polymerization (SeRP) . Such system showed moderate to well‐controlled polymerization behavior for most of the vinyl monomers, such as styrene, (meth)acrylates, vinyl acetate, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] They found that after oxidation or reduction, the hydrophobicity of the polymers could be enhanced, which reported the LRP of vinyl monomers based on the diselenocarbonyl compounds, e.g., selenium-mediated radical polymerization (SeRP). [20][21][22] Such system showed moderate to well-controlled polymerization behavior for most of the vinyl monomers, such as styrene, (meth)acrylates, vinyl acetate, etc. Polymers with tailored structures were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the analog of selenium (Se) with sulfur (S) in electronic structure, selenium-based RAFT agents have also been explored in RAFT polymerization [23e25]. Recently, Zhu et al [25] synthesized seleniumbased RAFT agents and used them as the RAFT agents for vinyl acetate polymerization. They [24] also reported the RAFT polymerization of styrene using the similar phosphinodiselenoic esters under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Among different LRP techniques, such as atom transfer radical polymerization (ATRP) 5,6 and reversible addition-fragmentation chain transfer polymerization (RAFT), 7 seleno-mediated radical polymerization (SeRP) [8][9][10][11] has been demonstrated as an alternative method applicable for various monomers. 4 Among different LRP techniques, such as atom transfer radical polymerization (ATRP) 5,6 and reversible addition-fragmentation chain transfer polymerization (RAFT), 7 seleno-mediated radical polymerization (SeRP) [8][9][10][11] has been demonstrated as an alternative method applicable for various monomers.…”
Section: Introductionmentioning
confidence: 99%